PGC-1α activity and mitochondrial dysfunction in preterm infants - Mohammadi, Atefeh; Higazy, Randa; Gauda, Estelle B. (Frontiers in Physiology, 2022)
Extremely low gestational age neonates (ELGANs) are born in a relatively hyperoxic environment with weak antioxidant defenses, placing them at high risk for mitochondrial dysfunction affecting multiple organ systems including the nervous, respiratory, ocular, and gastrointestinal systems. The brain and lungs are highly affected by mitochondrial dysfunction and dysregulation in the neonate, causing white matter injury (WMI) and bronchopulmonary dysplasia (BPD), respectively. Adequate mitochondrial function is important in providing sufficient energy for organ development as it relates to alveolarization and axonal myelination, and decreasing oxidative stress via reactive oxygen species (ROS) and reactive nitrogen species (RNS) detoxification. Peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1αlpha) is a master regulator of mitochondrial biogenesis and function. Since mitochondrial dysfunction is at the root of WMI and BPD pathobiology, exploring therapies that can regulate PGC-1α activity may be beneficial. This review article describes several promising therapeutic agents that can mitigate mitochondrial dysfunction through direct and indirect activation and upregulation of the PGC-1alpha pathway. Metformin, resveratrol, omega 3 fatty acids, montelukast, L-citrulline, and adiponectin are promising candidates that require further pre-clinical and clinical studies to understand their efficacy in decreasing the burden of disease from WMI and BPD in preterm infants.